Prospective of Emerging DNA and RNA Editing Tools for Environmental Challenges - Anisa Ulhusna (The Indonesian Green Technology Journal, 2021)
In a span of a decade, CRISPR-based system has been exponentially exploited in a wide range of applications. The majority of its utilization comes from the therapeutic field, serves as powerful gene therapy tools for many untreated diseases, and accelerates the understanding of complex diseases. In account of the robustness and the discovery of Cas enzymes with their distinctive properties, now it is possible to widen CRISPR application to another study field, including in tackling environmental issues. In this review paper, the most recent development of CRISPR utilization in environmental-linked studies is discussed in four different aspects, which are (1) role of CRISPR in biofuel production; (2) role of CRISPR in agricultural science; (3) role of CRISPR in the ecological study; and (4) role of CRISPR in water contaminant detection. The studies show that CRISPR can serve as a powerful genomic editing and detector tool in environmental studies, and the rooms for development are still wide open to improving its versatility in this field.